Steroidogenesis Mechanism, Disruption Factor, Gene Function, and Role in Male Fertility : A Mini Review - I Gede Widhiantara; Anak Agung Ayu Putri Permatasari; I Wayan Rosiana; Putu Angga Wiradana; BagusKomang Satriyasa (Indian Journal of Forensic Medicine & Toxicology, 2021)
Male fertility can be defined as the ability of the male reproductive system to impregnate a woman, whileinfertility is the condition of a married couple who have been married for one year or more and have had sexualintercourse regularly or without using contraception but do not have a pregnancy or offspring. About 10% ofmarried couples experience infertility. The main organ of male reproduction is the testes because in the testesthe process of forming spermatozoa and the hormone testosterone occurs. The hormone testosterone plays adirect role in the continuity of spermatogenesis. Testosterone is produced through a series of steroidogenesismechanisms in testicular Leydig cells. Several factors influence the course of steroidogenesis such as Leydigcells, steroidogenesis proteins, related genes to the influence of free radicals. These factors are closelyrelated to diet and lifestyle. This study is important to understand in efforts to prevent infertility in men.